Taxonomic revision of the Australian Eucarpiini (Hemiptera: Fulgoromorpha: Cixiidae) with the description of nine new species - Löcker, Birgit; Fletcher, Murray J.; Gurr, Geoff M. (Zootaxa, 2010)
The Australian planthopper tribe Eucarpiini is revised taxonomically. Five genera are recognised in the Australia fauna: Bajauana Distant 1907, Dilacreon Fennah, 1980, Kirbyana Distant, 1906, Neocarpia Tsaur & Hsu, 2003 and Nesochlamys Kirkaldy, 1907. Except for Bajauana all of these represent new records for Australia. Eucarpia Walker, 1857 is declared absent from Australia. Twelve species, nine of which are new, are recognised in the Australian fauna: Bajauana acuminata, sp. nov., Dilacreon akethe, sp. nov., D. ispi, sp. nov., Neocarpia rhizophorae, sp. nov., Nesochlamys capensis, sp. nov., N. contrarius, sp. nov., N. jubatus, sp. nov., N. pandikros, sp. nov. and N. yiralli, sp. nov. Except for Bajauana austrina (Kirkaldy, 1907) and D. (D.) granulinervis, all species are endemic to Australia. Lectotypes are designated for Australoma austrina Kirkaldy, 1907, Ptoleria australis Muir, 1913 and P. granulinervis Muir, 1913. New combinations proposed are: Dilacreon (Dilacreon) granulinervis (Muir, 1913) comb. nov. (from Eucarpia), Kirbyana australis (Muir, 1913) comb. nov. (from Eucarpia) and Leptolamia praetextata comb. nov. (from Bajauana, transfer from Eucarpiini to Cixiini). All Australian species of Eucarpiini are described and illustrated and identification keys to genera and species are provided.